Pengaruh Aplikasi Pupuk Kasgot dan NPK 16:16:16 terhadap Pertumbuhan Bibit LCC (Mucuna bracteata) - Anyi, Patrisius; Avianto, Yovi; Rahayu, Enny (AGROISTA : Jurnal Agroteknologi, 2025)
One of the most crucial phases for successful oil palm plantations is replanting management. One way to suppress weed growth in immature plantations (TBM) is by using tissue culture methods, namely planting legume cover crops (LCC). One type of LCC that grows very quickly is Mucuna bracteata. This study aimed to determine the effect of organic compost and NPK 16:16:16 fertilizer on the growth of Mucuna bracteata LCC seedlings. The study was conducted from October to December 2024 at KP2 INSTIPER Yogyakarta in Wedomartani Village, Depok District, Sleman Regency. The average temperature was 27°C to 30°C, and the elevation was 118 meters above sea level. This study used a completely randomized design (CRD) method with two factors. The first factor was the dose of Kasgot organic fertilizer consisting of four levels, namely control (0 g/plant), 4 g/plant, 8 g/plant, and g/plant. The second factor was the dose of NPK 16:16:16 fertilizer with four levels, namely control (0 g/plant), 2 g/plant, 4 g/plant, and 6 g/plant. The research data were analyzed using the analysis of variance (ANOVA) test at a 5% significance level and the DMRT further test. The results showed that there was no significant interaction between the dose Kasgot fertilizer and NPK fertilizer in influencing the growth of Mucuna bracteata. In addition, none of the treatments had a significant effect on plant growth.